Beyond survival … - Matthews, Ron (Taylor & Francis, 2025)
The purpose of this closing paper is to “draw threads” from the collection of papers presented in this Special Issue, with the aim of exploring the defence industrialisation experiences of small and medium powers. Structurally, the paper begins by examining the challenges Tier Two and Three nations face in developing and sustaining defence industries. Attention then switches to assessing the coping strategies these countries adopt in seeking to overcome the limitations imposed by constricted scale and defence economic infrastructure. Government has an important role to play in addressing trade-offs linked to the autonomy, dependence, and efficiency trilemma. The aim is to ensure that the required degree of indigenous defence industrial capacity offers an acceptable level of sovereignty and manufacturing efficiency that is also affordable. The final section speculates on the future defence industrial opportunities and threats Tier Two and Three states are likely to confront. Whatever the future holds, there is a sense from the case studies presented that small and medium powers can survive the constraints of relative smallness and prosper.
Keywords: 44 Human Society; Generic health relevance; 4408 Political science; small and medium defence powers; strategic autonomy; defence-industrial ecosystem; MCF strategies; civil-military integration